Coachella Canal lining project: cost effective construction for large scale water conservation - Charlton, Daniel, author; Dahl, Wayne, author; Dull, Chris, author; Steele, Ken, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The Coachella Canal Lining Project (CCLP), completed in 2007, is conserving over 26,000 AF of water per year. The project assists California in meeting its water needs while staying within its entitlement of Colorado River water of 4.4 million AFY and achieving water usage goals established under the Quantification Settlement Agreement. The project also provides water to settle a long standing water rights issue on the San Luis Rey River in California. To date, the total cost of the project is approximately $120 million including design, construction, environmental mitigation, and supervision and administration. Funding was provided by the California Department of Water Resources in the amount of $83.65 million, with the San Diego County Water Authority responsible for the remaining costs. The Bureau of Reclamation completed construction of the Coachella Canal in 1948. The canal is operated and maintained by Coachella Valley Water District (CVWD). CVWD administered the design, construction, and environmental aspects of the CCLP. The project was designed and constructed in accordance with Reclamation standards and administered by the CCLP Coordinating Committee composed of CVWD, SDCWA, and a mutually agreed chairman with participation by Reclamation, the San Luis Rey Settlement parties, and other interested parties. The CCLP lined approximately 36.5 miles or about one-third, of the 123 mile canal. The northern 38 miles of the canal was lined in 1948 during original construction and the southern 49 miles of the canal was lined in 1981 by the Bureau of Reclamation. The project was originally envisioned to consist of lining the existing canal section, however, following the 60 percent design review, the project was revised to construct a new adjacent parallel canal at significant cost savings. The project involved 5.7 million cy of excavation, 1.3 million sq yds of 3-inch thick concrete paving, construction of 25, 10.5 by 10.5-foot double barrel inverted siphons, six new check structures, over 60 miles of deer fence and 56 wild game drinkers.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.